MEANINGS AND SENSES OF STUDENTS IN THE PEDAGOGY DEGREE PROGRAM REGARDING SUPERVISED INTERNSHIP IN YOUTH AND ADULT EDUCATION IN BRAGANÇA, PARÁ, BRAZIL - Maciel, Rogerio Andrade; da Silva Junior, Sebastião Rodrigues; Mendes, Wallace Benedito Silva; Moura, João Felipe (Seven Editora, 2026)
This article presents an analysis of the senses and meanings that students attributed to the Supervised Internship in Youth and Adult Education (ESEJA), carried out in the Pedagogy degree course at the Federal University of Pará, Bragança University Campus. The methodology used a qualitative approach and employed field and documentary research for data collection. In the data analysis, the most significant words from the interns were selected, allowing the construction of a web of meanings and senses about ESEJA. The results revealed that the set of theoretical refinements constituted in the classroom and the experiences developed through observation and research in the daily life of the school, up to the applicability of the intervention project, enabled numerous meanings for the Pedagogy graduates. Thus, they were guides to the set of meanings that generate sense about ESEJA.